2015
DOI: 10.4102/jsava.v86i1.1221
|View full text |Cite
|
Sign up to set email alerts
|

Beyond traditional dairy veterinary services: ‘It’s not just about the cows!’

Abstract: It remains a challenge for the role of the dairy veterinarian to move beyond that traditionally held. In larger herds with a high reproductive workload, we are at great risk of becoming specialist technicians. Instead we seek greater involvement, to deliver comprehensive services and to be recognised for them, personally and financially. Given the frequency of our visits, knowledge and analytical skills we are in a unique position to provide inputs that complement advice given by other consultants. Failure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The respondents also stressed that maintaining cattle health, cleanliness, and disease control are essential for maximizing milk production. They highlighted the challenges of middle-and low-income countries in ensuring cattle health and nutrition (Martin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The respondents also stressed that maintaining cattle health, cleanliness, and disease control are essential for maximizing milk production. They highlighted the challenges of middle-and low-income countries in ensuring cattle health and nutrition (Martin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variation is a threat for correct data interpretation as people are eager to use averages for evaluating and comparing group or herd parameters. Averages usually hide those individual animals that need special attention (van der Leek 2015).…”
Section: Features Of a Key Performance Indicatormentioning
confidence: 99%
“…Veterinarians are in a unique position to offer advice to dairy producers given their education, analytical skills, and frequency of farm visits (Van der Leek, 2015). Guterbock (2001) and Cannas da Silva et al (2010) suggested that veterinarians can observe and monitor animal-related activities on the farm and provide support to the dairy producer regarding management, reproduction, animal welfare, milk quality, and profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Guterbock (2001) and Cannas da Silva et al (2010) suggested that veterinarians can observe and monitor animal-related activities on the farm and provide support to the dairy producer regarding management, reproduction, animal welfare, milk quality, and profitability. Van der Leek (2015) suggested that failure to provide support leads to economic consequences for the dairy farm.…”
Section: Introductionmentioning
confidence: 99%